MEMBANGUN KESERASIAN SOSIAL MELALUI BUDAYA DUAN LOLAT PADA MASYARAKAT WUNLAH, KEPULAUAN TANIMBAR - Cornelly M.A. Lawalata; Max Maswekan (JURNAL BADATI, 2023)
The Tanimbar people in general, particularly in Wunlah Village, have a culture called duan lolat which was formed by marriage between a man and a woman. In daily life, Duan is addressed as Uncle or Uncle. Duan is formed or born because the sister of a man who has a daughter (daughter), while Lolat is formed because the daughter (daughter) of a sister who marries a man or a man who becomes her husband. In essence, Duan is the male family as the giver of the virgin (daughter), while Lolat is the female family as the recipient of the virgin. This study aims to determine the cultural value of Duan Lolat in building social harmony in Wunlah Village, Wuarlabobar District, Tanimbar Islands Regency. The method used is a qualitative method, with community informants related to the problem under study. From the results of the research it is known that Duan's responsibility is to choose (determine) a mate for his sister's sons, pay for his marriage property, and protect his Lolats. While Lolat has the responsibility to work and serve Duan whether asked or not, to provide fishing or fishing products or other types of food to Duan and to respect and value Duan because of the status he bears. Duan and Lolat have the function of mutually protecting, supporting, and enlivening. Duan existed and grew up because of Lolat. On the other hand, Lolat existed and was strong because of Duan. That is, the relationship between Duan and Lolat is not a hierarchical or top-down relationship, but an equal, balanced and mutually reinforcing relationship (symbiosis-mutualistic) in unity and harmony. This relationship is based on the values of equality, brotherhood, kinship, justice, equity and balance. Therefore, the cultural value of Duan Lolat is a relationship that functions to build social harmony in people's lives and integrate the Tanimbar community in general, and especially in Wun Village, which is inherited and maintained from generation to generation.